The Emotional Interaction of Judicial Objectivity - Bergman Blix, Stina (Oñati Socio-Legal Series, 2019)
Like other Western legal systems, the Swedish legal system constructs objectivity as an unemotional state of being. We argue that the enactment of objectivity in situ relies on objectivity work including emotion management and empathy. Building on qualitative interviews and observations in Swedish district courts, we analyse courtroom interaction through a dramaturgical lens, highlighting tacit signals and interprofessional emotional communication aimed to secure objective procedures, while sustaining the ideal of unemotional objectivity. By analytically separating objectivity from impartiality, we show that judges’ objective performances balance empathic attunement and restrained expressions to uphold an impartial presentation. Prosecutors take pride in maintaining objectivity in spite of being partial, fostering the ability to switch between engagement and disengagement depending on the strength of the case. The requirement for legal professionals to be autonomous demands skillful inter-professional emotional attuning. Thereby, collaborative professional emotion management achieves the ideal of justice as being objective.